Pengaruh Penggunaan Video Animasi terhadap Hasil Belajar Matematika Peserta Didik Kelas IV SDN 35 Pontianak Selatan - Nur Khalid Saifullah; Hamdani Hamdani; Dyoty Auliya Vilda Ghasya (AS-SABIQUN, 2023)
The purpose of this study was to analyze the effect of using video animation on the mathematics learning outcomes of fourth grade students at SDN 35 Pontinak Selatan by conducting experimental research in the form of Nonequivalent control group research. The research sample consisted of 30 students in class IV A (control class) and 30 students in class IV B (experimental class) at SDN 35 Pontianak Selatan. Data collection techniques use measurement techniques with instruments in the form of essay questions. The results of the pre-test and post-test calculations for the experimental class were 59.67 and 82.33. While the pre-test and post-test results for the control class were 59.17 and 72.50. Based on the results of calculations using the effect-size formula, it can be concluded that the use of animated videos has an effect on student learning outcomes in class IV material at SDN 35 Pontianak Selatan with a value of 0.68 which is included in the medium category.